Lessons from the Bakken Oil Patch - Caraher, William; Weber, Bret; Rothaus, Richard (Journal of Contemporary Archaeology, 2017)
This article summarizes the recent work of the North Dakota Man Camp Project to understand the largely undocumented migrants arriving in the Bakken Oil Patch for work. It argues that efforts to document short-term labor in the Bakken exposes particular challenges facing the archaeology of the modern world ranging from the ephemerality of short-term settlements to the hyper-abundance of modern objects. The use of photography, video, interviews, and descriptions produced an abundant archive of archaeological ephemera that in some ways parallels the modern character of temporary workforce housing. The final section of this article offers some perspectives on how work in the Bakken oil patch can inform policy, our understanding of material culture in the modern world, and the role of the discipline in forming a shared narrative.